2006
DOI: 10.5194/acp-6-2727-2006
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric carbon gases retrieved from SCIAMACHY by WFM-DOAS: version 0.5 CO and CH<sub>4</sub> and impact of calibration improvements on CO<sub>2</sub> retrieval

Abstract: Abstract. The three carbon gases carbon monoxide (CO), carbon dioxide (CO 2 ), and methane (CH 4 ) are important atmospheric constituents affecting air quality and climate. The near-infrared nadir spectra measured by SCIAMACHY on ENVISAT contain information on the vertical columns of these gases which we retrieve using a modified DOAS algorithm (WFM-DOAS or WFMD). Our main data products are CO vertical columns and dry-air column averaged mixing ratios of methane (CH 4 ) and CO 2 (denoted XCH 4 and XCO 2 ). Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(100 citation statements)
references
References 47 publications
5
95
0
Order By: Relevance
“…Bösch et al [33] use X CO 2 Park Falls data to reveal biases in the SCIAMACHY data. De Beek et al [34], Buchwitz et al [35] and Reuter et al [36,37] have significantly improved the SCIAMACHY retrieval algorithms, again using TCCON data as their ground reference.…”
Section: (B) Satellite Validationmentioning
confidence: 99%
“…Bösch et al [33] use X CO 2 Park Falls data to reveal biases in the SCIAMACHY data. De Beek et al [34], Buchwitz et al [35] and Reuter et al [36,37] have significantly improved the SCIAMACHY retrieval algorithms, again using TCCON data as their ground reference.…”
Section: (B) Satellite Validationmentioning
confidence: 99%
“…Between 2003 and 2012, the Scanning Imaging Absorption spectrometer for Atmospheric CartograpHY (SCIA-MACHY) was operated on board the ESA ENVIronmental SATellite (ENVISAT), providing nearly 10 years of XCH 4 sensitive to the atmospheric boundary layer (Burrows et al, 1995;Buchwitz et al, 2006;Dils et al, 2006;. These satellite retrievals were the first to be used for global and regional inverse modelling of methane fluxes (Meirink et al, 2008a;Bergamaschi et al, 2007Bergamaschi et al, , 2009).…”
Section: Satellite Data Of Column-averaged Chmentioning
confidence: 99%
“…These measurements form a record of integrated net CO 2 exchange from multiple processes, geographic areas, and times (Peters et al 2007). Retrievals of XCO 2 from the near-infrared nadir spectral radiance and solar irradiance measurements of the SCIAMACHY satellite instrument between 2003 and 2005 are compared with global XCO 2 obtained from CarbonTracker, which showed that the measured CO 2 year-toyear increase agrees within about 1 ppm/year with CarbonTracker (Buchwitz et al 2006). The Carbon Tracker was used to estimate net ecosystem CO 2 exchange over China for the period from 2001 to 2010, in which additional Chinese and Asian CO 2 observations were input to improve its estimation accuracy (Zhang et al 2014a).…”
Section: Classical Methodsmentioning
confidence: 99%